TU7.7 Cheques and Balances: A Five Year Review of Surgical Settlements. (9th August 2022) - Clements, Caterina; Bezzaa, Sabrina; Curwen, Oliver; Vance-Daniel, Joseph; Lewis, Trystan; Nehra, Dhiren
Abstract: Aim: The litigious burden in the NHS has been increasing yearly, costing an estimated £2.5 billion per year in financial settlements. We investigated the causes of general surgical settlements and attributed costs at a district general hospital over a five-year period. Method: A retrospective analysis of all general surgical claims between 2016–2021 using the NHS Resolutions Case Management System. Selected cases were those which resulted in out of court financial settlements; whilst these claims have been settled, the trust admitted no negligence in each case. Results: A total of 12 settlements were made with a total cost of £249, 918 (£8000-£60, 000, mean £20, 827). Eight of the claims (67%) related to elective cases with four (33%) emergency cases. Of the total cases, 41% and 33% related to management of gallstones and appendicitis respectively. The majority of claims (58%) related to delays in treatment with a total cost of £103, 500 (£8000-£35, 000), accounting for 41% of total settlement costs. Five cases (42%) were due to harm with a combined total of £146, 418 (£9000-£60, 000), 59% of the total settlement. Of the claims due to harm, 80% suffered recognised complications of the procedure. Conclusions: Increasing litigation in the NHS over the last decade now accounts for 2% of the total NHS budget. The majority of settlements reviewed here were for avoidable delays in elective treatment, with higher financial settlements for well documented surgical complications related to the consent process. Better access to investigations, earlier clinical review, and reductions in delays to elective surgeries may reduce the financial burden of litigation.